Kallmann's syndrome: mirror movements associated with bilateral corticospinal tract hypertrophy. - Krams, M; Quinton, R; Ashburner, J; Friston, K; Frackowiak, R; Bouloux, P; Passingham, R (1999)
OBJECTIVE: To investigate the etiology of mirror movements in patients with X-linked Kallmann's syndrome (xKS) through statistical analysis of pooled white matter data from structural MR images. BACKGROUND: Mirror movements occur in 85% of xKS patients. Previous electrophysiologic studies have suggested an abnormal ipsilateral corticospinal tract projection in xKS patients exhibiting mirror movements. However, an alternative hypothesis has proposed a functional lack of transcallosal inhibitory fibers. METHODS: T1-weighted brain scans were normalized into stereotaxic space with segregation of gray and white matter to allow comparison of pooled white matter data on a voxel-by-voxel basis using SPM-96 software. Nine xKS patients were compared with two age-matched groups of nonmirroring individuals: nine patients with autosomal Kallmann's syndrome (aKS) and nine age-matched normal (healthy) men. RESULTS: Hypertrophy of the corpus callosum was found in both Kallmann's syndrome groups: the anterior and midsection in xKS, and the genu and posterior section in aKS. Bilateral hypertrophy of the corticospinal tract was found only in the group of xKS patients exhibiting mirror movements. SPM analysis was validated by an independent region of interest analysis of corpus callosum size. CONCLUSION: Although morphometry on its own cannot determine the cause of mirror movements, the specific finding of a hypertrophied corticospinal tract in xKS is consistent with electrophysiologic evidence suggesting that mirror movements in xKS result from abnormal development of the ipsilateral corticospinal tract fibers.